(untitled) (American Journal of Islam and Society, 1994)
The goal of this paper is b examine the extent to which religiosity, within the Islamic context, can be viewed BS an effective mechanism against criminal temptation. To accomplish this, we will a) review the theories and literatwe concerning the religion-crime relationship, b) discuss the meaning of the religiosity concept in order to highlight essential features of religiosity in Islam that make it a valuable force in crime control within a Muslim society, and c) present a thorough discussion of certain elements of Islamic ideology that conshin criminal behavior. Theoretical Antecedence The relation of religion to other social phenomena has received a great deal of attention from social scientists. Given the variations of the ideological and philosophical backgrounds underlying most schools of SQcia1 thought, theme is no single view of the impact of religion. For example, Ibn Khaldiin ([d. 14061 1981) views religion, through its effect on social cohesion and cooperation, as a primary factor in the rise and fall of Societies. Marx (Tucker 1978), in his analysis of capitalism, recognizes the importance of religion as a control mechanism and considers it an effective instNment utilized by the bourgeois dass to maintain its dominance over the proletariat. On the conttary, Weber (1958) views the entin= capitalist system as a by-product of Protestantism. But it is perhaps the functional theorists who highlight the impowce of religion on the creation and maintenance of social order. They consider religion to be the basis and source of social values and norms by which people are united and their behavior and activities are regulated murkheim 1951). However, due to the increasingly secular nature of modem ...